'I don't feel like I'm learning how to be a doctor': early insights regarding the impact of Covid-19 on UK medical student professional identity. (2022) - Harvey, Anna; , Megan E L Brown; , Matthew H V Byrne; , Laith Alexander; Wan, Jonathan CM; Ashcroft, James; Schindler, Nicholas; Brassett, Cecilia
No abstract available